Mídia, cognição e poder: uma leitura corpomídia da lei Cidade Limpa - Pasqualini, Diógenes José (2011)
The current mayor of Sao Paulo, Gilberto Kassab, was elected deputy mayor in José Serra's government in 2004. When Serra left office to become Governor of the State of São Paulo, he assumed command of the administrative municipality. He gained notoriety by presenting a controversial proposal, which became a law in São Paulo, law n. 14.233 of 2006. It became known as "Clean City Law", and determines the use of the urban landscape in the county. Upon gaining a place and providing guidelines for the media, the "Clean City Project," he gained prominence in the media, and political force, and as a politician with a modest political career, (he had been a city councilman and deputy), he went on to be elected mayor of the largest city in Latin America. He won the elections in 2008 by defeating the two candidates who were considered, up until that time, more "experienced" in politics: former Sao Paulo Governor Geraldo Alckmin and the former mayor of São Paulo, Marta Suplicy. The hypothesis argued here is that this Law gave rise to the political marketing strategy used in the election of Gilberto Kassab for the post of Mayor of Sao Paulo. The proposed "clean the city" of its visible pollution became a powerful metaphor. The cleaning concept embodied the ideal city to live in, free of problems, more humane, safe, an orderly city, free of its ills. To investigate the effect of this Law and its effect on voters the metaphorical theory Corpomídia will be used (Katz & Greiner), which expands the understanding of the relationship between the body, through its mediation and how the massification of a proposal for cleaning captured people around an idea